A Hecke-equivariant decomposition of spaces of Drinfeld cusp forms via representation theory, and an investigation of its subfactors - Böckle, Gebhard; Gräf, Peter Mathias; Perkins, Rudolph (Research in number theory, 2021)
There are various reasons why a naive analog of the Maeda conjecture has to fail for Drinfeld cusp forms. Focussing on double cusp forms and using the link found by Teitelbaum between Drinfeld cusp forms and certain harmonic cochains, we observed a while ago that all obvious counterexamples disappear for certain Hecke-invariant subquotients of spaces of Drinfeld cusp forms of fixed weight, which can be defined naturally via representation theory. The present work extends Teitelbaum’s isomorphism to an adelic setting and to arbitrary levels, it makes precise the impact of representation theory, it relates certain intertwining maps to hyperderivatives of Bosser-Pellarin, and it begins an investigation into dimension formulas for the subquotients mentioned above. We end with some numerical data for $$A={\mathbb {F}}_3[t]$$that displays a new obstruction to an analog of a Maeda conjecture by discovering a conjecturally infinite supply of $${\mathbb {F}}_3(t)$$-rational eigenforms with combinatorially given (conjectural) Hecke eigenvalues at the prime t.